The relationship between learning approaches and academic achievement among INTEC students, UiTM Shah Alam / Hanin Naziha Hasnor - Hasnor, Hanin Naziha (2011)
The main aim of this study was to examine the influence of three different learning approaches which are Deep Approach, Surface Approach and Strategic Approach on students' academic achievement among the American Programme students of International Education College (INTEC), UiTM Shah Alam. The study also investigated the relationship between the variables involved and determined the predictors of academic achievement. The design of this research is descriptive in nature and questionnaires were used to obtain information on students' preferred learning approaches and their level of academic achievement. A total of 233 students responded to the questionnaire. The findings show that students are more prone to use Deep Approach to studying. The findings also revealed that there is an inverse relationship between Surface Approach and academic achievement. In terms of determining the contributions of the significant predictive power of learning approaches in explaining academic achievement, the result revealed that 3.6% of the variance in academic achievement is explained by Surface Approach. Implications for teaching and learning were also discussed.